Faktor Faktor yang Mempengaruhi Mahasiswa Kota Batam dalam Memilih Jalur Karir Akuntansi - Amielia Eka Putri Galu Mabela; Erni Yanti Natalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find whether intrinsic motivation, extrinsic motivation, and career exposure can influence students in choosing an accounting career path. This research contains 298 samples of active accountant students at Kota Batam taken from Universitas Internasional Batam, Universitas Riau Kepulauan, Universitas Universal and Universitas Batam. The method used in this research is quantitative with a Multiple Linear Regression statistic approach. To conduct this research, descriptive statistical tests, data quality tests, classical assumptions, multiple regression tests, coefficients of determination, and hypothesis tests are employed. The findings of this research are, intrinsic motivation partially influences students in choosing an accounting career path, extrinsic motivation partially influences the in choosing an accounting career path, career exposure partially influences the student in choosing an accounting career path. All of the variables simultaneously influence student accountants’ career path. Exposure career is the greater influence to students in choosing an accounting career path due to its coefficient regression score which is higher than independent variables. We suggest for future research to use the factor of a third person or use other factors such as motivation for overseas job opportunities.